Conjunctiva, Cornea, Sclera Injuries - Afsun Şahin (Türk Oftalmoloji Dergisi, 2012)
Anterior segment traumas are one of the most important causes of blindness. Since most of the work-related eye injuries are avoidable by protective glasses, education by ophthalmologists gains more importance. Knowing the main pathogenetic mechanisms and treatment options would contribute to successful long-term treatment and visual rehabilitation in traumatized eyes. Detailed history, visual acuity, examination of eye lids and adnexa, palpation of the orbital rim, assessment of eye movements, examination of cornea and conjunctiva (sterile fluorescein drops, Seidel test), assessment of anterior chamber, pupillary examination (size, shape, reaction), status of the lens, and fundus examination are performed in case of eye injury. Multi-step approach is performed depending on the type of the trauma. The aim of this review is to analyze the current treatment approaches to conjunctiva, cornea, and sclera injuries. (Turk J Ophthalmol 2012; 42: Supplement 23-6)